Exploratory groundwater modelling in data-scarce environments : the shallow aquifer of River Yobe Basin, North East Nigeria - Hassan, M. (Cranfield University, 2002)
This thesis addresses the issues of modelling a groundwater system in a data-scarce environment, the Yobe river basin, north east Nigeria. Despite significant investment in the past towards water resources developments, basic data on groundwater resources are limited. Short-term studies by Consultants contain some weaknesses and have not fully investigated the mechanisms of flow to and from the aquifer. Fieldwork studies conducted during this work and in the past (Alkali, 1995) showed that the shallow aquifer system is hydrogeologically complex. Concerns such as the relative magnitudes of recharge mechanisms to the aquifer, hydrologic conditions of the aquifer, a large change in river stage, presence of unconfined 'windows' for vertical recharge, and the fact that the region is located in a semi-arid region need to be addressed. This increased the concerns for the need to explore the system through modelling. Modeling can give insights into the whole system behaviour which other approaches cannot provide. Therefore modelling was carried out and it has provided valuable insights into the complex system. This thesis reports on the procedure of developing a groundwater model that is basic and exploratory based on limited data. Detailed conceptual model was developed using data from previous workers and from a fieldwork undertaken in this study. The conceptual model provided key hydrogeological information on the various physical processes and how they interact with the shallow Fadama alluvial aquifer. It describes the aquifer as around 10 m thick and about 4 km wide with the river partially penetrating it. The aquifer consists of areas that are confined and some that are unconfined. The river is ephemeral and its stage changes rapidly over 4 m. Recharge mechanisms to the aquifer consist of vertical recharge from rainfall and overland flooding through permeable topsoil, river to aquifer flow and 'leakage' through low permeability cover. The conceptual model was idealized and translated into a computational groundwater model using MODFLOW. The model investigated the role of each components of flow in determining the overall water balance of the system. The relationship between river stage and river coefficient in the study of river-aquifer interaction was investigated. Finally the response of the aquifer system to pumping was explored. Groundwater head output from the model was used in the calculation of the various flow components. The main findings and conclusions of the work are that: (i) a comprehensive conceptual model is fundamental in developing a numerical groundwater model; (ii) the exploratory model developed using limited data is plausible because it is hydrologically credible and fits the available data; (iii) the water balance shows that the river to aquifer flow dominates the recharge from rainfall and overland flooding. Contrary to initial belief, the largest river to aquifer flow occurs before the river reaches its peak; (iv) flows between river and aquifer are insensitive to variation of river coefficient with river stage. The limiting factor in the exchange of water between them is the hydraulic gradient and the transmissivity of the aquifer; (v) in representing the river with a constant river coefficient, the coefficient has a threshold value above which the river-aquifer interaction does not change significantly; (vi) over-pumping of the aquifer will decrease river flow to disadvantage of downstream users; (vii) the replenishment of the aquifer can be improved by pumping it at a modest rate.